Pesantren Tradition and the Existence of Tarekat Syattariyah in the Java War of 1825-‎‎1830‎ - Moh Ashif Fuadi; Moh. Mahbub; Martina Safitry; Usman Usman; Dawam Multazamy Rohmatulloh; M. Harir Muzakki (Universitas Darussalam Gontor, 2022)
The Java War had its unique influence on the development of pesantren. Prince Diponegoro plays the struggle against the invaders with some of his soldiers who come from among the pesantren. After his defeat in the Java War of 1825-1830, many Diponegoro warriors spread to teach religion. This research will discuss the sustainability of the struggle of Diponegoro warriors in pesantren and the Islamic treasures of the Java War, such as strengthening pesantren traditions and the existence of tarekat syattariyah (syattariyah order). This research is classified as historical research through Kuntowijoyo's historical research methods: topic selection, heuristics, verification, interpretation, and historiography. This research yielded several conclusions, namely: First, after its defeat in the Java war, the struggle of Diponegoro warriors with a cleric-santri background continued through the establishment of pesantren with a change in strategy more to intellectual strengthening. Second, intellectual traditions during the Java War, one of which was through the study of yellow books typical of pesantren with fiqh and Sufi patterns such as Fatḥ al-Qarîb and Tuḥfah al-Mursalah ila Rûḥ al-Nabiy. Third, the existence of the tarekat syattariyah that had an anti-colonial character at that time was quite popular in Java, made the order followed by prince Diponegoro and some of his soldiers. Fourth, when compared to the Padri War, the typology of da'wah struggle developed by Diponegoro warriors is more moderately patterned identically to Walisongo's accommodating character.